MiR-146a as marker of senescence-associated pro-inflammatory status in cells involved in vascular remodelling - Olivieri, Fabiola; Lazzarini, Raffaella; Recchioni, Rina; Marcheselli, Fiorella; Rippo, Maria Rita; Di Nuzzo, Silvia; Albertini, Maria Cristina; Graciotti, Laura; Babini, Lucia; Mariotti, Serena; Spada, Giorgio; Abbatecola, Angela Marie; et al. (AGE, 2013)
In order to identify new markers of vascular cell senescence with potential in vivo implications, primary cultured endothelial cells, including human umbilical vein endothelial cells (HUVECs), human aortic endothelial cells (HAECs), human coronary artery endothelial cells (HCAECs) and ex vivo circulating angiogenic cells (CACs), were analysed for microRNA (miR) expression. Among the 367 profiled miRs in HUVECs, miR-146a, miR-9, miR-204 and miR-367 showed the highest up-regulation in senescent cells. Their predicted target genes belong to nine common pathways, including Toll-like receptor signalling (TLR) that plays a pivotal role in inflammatory response, a key feature of senescence (inflammaging). MiR-146a was the most up-regulated miR in the validation analysis (>10-fold). Mimic and antagomir transfection confirmed TLR’s IL-1 receptor-associated kinase (IRAK1) protein modulation in both young and senescent cells. Significant correlations were observed among miR-146a expression and β-galactosidase expression, telomere length and telomerase activity. MiR-146a hyper-expression was also validated in senescent HAECs (>4-fold) and HCAECs (>30-fold). We recently showed that CACs from patients with chronic heart failure (CHF) presented a distinguishing feature of senescence. Therefore, we also included miR-146a expression determination in CACs from 37 CHF patients and 35 healthy control subjects (CTR) for this study. Interestingly, a 1,000-fold increased expression of miR-146a was observed in CACs of CHF patients compared to CTR, along with decreased expression of IRAK1 protein. Moreover, significant correlations among miR-146a expression, telomere length and telomerase activity were observed. Overall, our findings indicate that miR-146a is a marker of a senescence-associated pro-inflammatory status in vascular remodelling cells.